High‐throughput liquid chromatography/electrospray ionization–tandem mass spectrometry method using in‐source collision‐induced dissociation for simultaneous quantification of imatinib, dasatinib, bosutinib, nilotinib, and ibrutinib in human plasma. (18th April 2021) - Hirasawa, Tensei; Kikuchi, Masafumi; Shigeta, Kensuke; Takasaki, Shinya; Sato, Yu; Sato, Toshihiro; Ogura, Jiro; Onodera, Koichi; Fukuhara, Noriko; Onishi, Yasushi; Maekawa, Masamitsu; Mano, Nariyasu
Abstract: Recent studies have shown that therapeutic drug monitoring of tyrosine kinase inhibitors (TKIs) could improve treatment efficacy and safety. A simple analytical method using high‐performance LC/electrospray ionization–tandem mass spectrometry has been developed and validated for simultaneous quantification of BCR‐ABL and Bruton's TKIs used for chronic leukemia (imatinib, dasatinib, bosutinib, nilotinib, and ibrutinib) in human plasma. Although these structures and physical properties are similar, owing to their different linear ranges, simultaneously determining the plasma levels of these five TKIs by applying optimal MS parameters remains difficult. A quantitative range exceeding 60, 000‐fold was required, and the linear dynamic ranges of imatinib, bosutinib, and nilotinib were limited because of the presence of a saturated detection signal. In this study, we applied the in‐source collision‐induced dissociation technique to control the ion amounts in mass spectrometry. This new method allowed rapid determination within 5 min with simple pretreatment. The method was validated according to the US Food and Drug Administration guidelines. Moreover, all samples of patients with chronic leukemia were successfully measured and their values were within the linear range of measurement. Therefore, our high‐throughput analytical system is useful to measure the plasma concentrations of imatinib, dasatinib, bosutinib, nilotinib, and ibrutinib in clinical practice.